2018
DOI: 10.1007/s11265-018-1343-1
|View full text |Cite
|
Sign up to set email alerts
|

Extending the Lifetime of Nano-Blimps via Dynamic Motor Control

Abstract: Nano-sized unmanned aerial vehicles (UAVs), e.g. quadcopters, have received significant attention in recent years. Although their capabilities have grown, they continue to have very limited flight times, tens of minutes at most. The main constraints are the battery's energy density and the engine power required for flight. In this work, we present a nano-sized blimp platform, consisting of a helium balloon and a rotorcraft. Thanks to the lift provided by helium, the blimp requires relatively little energy to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 31 publications
(33 reference statements)
0
5
0
Order By: Relevance
“…https://www.decawave.com/sites/default/files/resources/ dw1000-datasheet-v2.09.pdf2 In our experiments, we observed that the optimization function, in the proximity of the global minimum, is always convex. Therefore, if the initialization value (i.e., x 0 , y 0 ) lies in this convex region, the optimizer quickly converges to the global minimum.…”
mentioning
confidence: 63%
See 1 more Smart Citation
“…https://www.decawave.com/sites/default/files/resources/ dw1000-datasheet-v2.09.pdf2 In our experiments, we observed that the optimization function, in the proximity of the global minimum, is always convex. Therefore, if the initialization value (i.e., x 0 , y 0 ) lies in this convex region, the optimizer quickly converges to the global minimum.…”
mentioning
confidence: 63%
“…In the last few years, unmanned aerial vehicles (UAVs) have been introduced in a wide range of industrial applications, such as aerial inspection and ambient awareness [1], [2], [3].…”
Section: Introductionmentioning
confidence: 99%
“…A ERIAL robots have been pushing the boundary of indoor capabilities by demonstrating application success in tasks such as surveillance and inspection [1]- [4]. However, existing aerial platforms have not developed the smooth and safe indoor operations necessary for human interaction.…”
Section: Introductionmentioning
confidence: 99%
“…Conventional unmanned aerial vehicles (UAV) that are capable of static hovering in most cases generate lift purely through rotor thrust, which typically drains their battery in under 20 minutes. LTA vehicles, on the other hand, are able to maintain a desired altitude for significantly longer periods of time on a single battery charge [1]. In addition, airship platforms…”
Section: Introductionmentioning
confidence: 99%